Demokrasi Partisipatif Pembentukan Peraturan Daerah: Analisis Yuridis Terhadap Peran DPRD Kabupaten Bima dalam Mewujudkan Pemerintahan Daerah yang Responsif - Ramdin; Erham; Hajairin (Legalita, 2026)
This study aims to analyze the regulation of participatory democracy in the formation of Regional Regulations and examine the role of the Regional House of Representatives (DPRD) of Bima Regency in realizing responsive local governance. The research employs an empirical juridical method with statutory, conceptual, and socio-legal approaches. The findings indicate that public participation in the formation of Regional Regulations has been normatively guaranteed under Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-Undangan and Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah; however, its implementation in Bima Regency has not been fully optimal. The DPRD of Bima Regency has implemented several mechanisms of public participation, including public consultations and public hearings, yet these mechanisms remain largely formalistic and have not fully provided substantive participatory space for the community. The study finds that obstacles to participatory democracy are influenced by juridical, structural, cultural, and technical factors, including weak technical regulations on public participation, domination of political elites, limited access to information, low public legal awareness, paternalistic political culture, limited participation forums, as well as budgetary and socialization constraints. Strengthening the role of the DPRD is necessary through optimizing public hearings, digitalizing local legislation, enhancing transparency in the Regional Legislative Program, involving vulnerable groups, and reinforcing transparency and accountability in local legislative processes to achieve more responsive, participatory, and democratic local governance.